Freinet and Montessori in practice. A comparative analysis of the meanings attributed to the process of learning by early education teachers – research report - Jendza, Jarosław; Grzanka, Joanna (Problemy wczesnej Edukacji, 2020)
The article presented is a qualitative analysis of the early education Freinet and Montessori teachers in relation to their educational practices in the scope of educational constructivism. Understanding constructivism as a metaphor describing process of learning, the authors outline similarities and differences in the conceptions attributed to the processes of learning between the two researched groups of teachers. The results of the analysis show the opposite “direction” of the thematizations. Freinet teachers concentrate on the techniques and then – in their narratives – outline the values related to education whereas Montessori teachers’ narratives are oriented at values and only illustrated with some technological examples. The outcomes of the analysis can be formulated in a form of provisional synthesis: The realization of constructivism in education is not connected so much with so called “active learning techniques” but rather with values, individual and shared axio-educational orientations and the quality of relations between various subjects involved in education. Such a hypothesis leads to the questioning of the tendency according to which teachers’ education should be practical. On the contrary, we claim that such a conception on teachers’ education might be an obstacle to the wide implementation of constructivism in educational practices.